Subacute cutaneous lupus erythematosus onset preceded by Kikuchi-Fujimoto disease - Di Lernia, Vito; Bajocchi, Gianluigi; Piana, Simonetta (Dermatology Practical & Conceptual, 2014)
Kikuchi-Fujimoto disease (KFD) is an uncommon clinicopathological entity characterized by fever and lymphadenopathy, predominantly involving cervical lymph nodes, accompanied by chills and leukopenia. The diagnosis relies primarily on the presence of typical morphological features in the swelling lymph nodes. KFD can occur as a benign and self-limiting lymphadenopathy, but it can sporadically precede, postdate or coincide with the diagnosis of systemic lupus erythematosus (SLE). The authors report a case of subacute cutaneous lupus erythematosus (SCLE) in a 42-year-old female preceded by prolonged fever, anemia, leukopenia, and cervical necrotizing lymphadenopathy. About two months later, the patient developed facial and scalp plaques suggestive of lupus skin disease. Histologic and immunologic investigations lead to the diagnosis of SCLE. It is not clear whether KFD associated with lupus skin disease are true KFD or a histopathologic feature of SLE.